2007
DOI: 10.1111/j.1365-2443.2007.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the Drosophila ANT gene by the DRE/DREF system

Abstract: Adenine nucleotide translocase (ANT) is a crucial component in the maintenance of cellular energy homeostasis, as well as in the formation of the mitochondrial permeability transition pores. However, the molecular mechanisms regulating the expression of the ANT gene are poorly understood. In this study, we have identified three DNA replication-related elements (DRE; 5′ ′ ′ ′-TATCGATA) in the 5′ ′ ′ ′-flanking region of the Drosophila ANT (dANT ) gene. Gel-mobility shift analyses revealed that all three of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…We first examined two independent lines that each contained a P-element insertion within the 5 0 region of the dref locus (dref KG09294 and dref NP4719 ). A previous report showed that the dref KG09294 flies had markedly reduced dref mRNA levels (Kim et al, 2007). We also observed that dref KG09294 cell clones in the mitotic larval wing disc show little or no DREF protein (Fig.…”
Section: Dref Is Required For Cellular and Organismal Growth In Drososupporting
confidence: 78%
“…We first examined two independent lines that each contained a P-element insertion within the 5 0 region of the dref locus (dref KG09294 and dref NP4719 ). A previous report showed that the dref KG09294 flies had markedly reduced dref mRNA levels (Kim et al, 2007). We also observed that dref KG09294 cell clones in the mitotic larval wing disc show little or no DREF protein (Fig.…”
Section: Dref Is Required For Cellular and Organismal Growth In Drososupporting
confidence: 78%
“…For this purpose, we carried out lacZ staining of both initial and flipped out lines of ME boundary in the Dref mutant background. We did not find any effect of Dref KG09294 on ME boundary although this allele is known to affect the function of this protein (61), (Supplementary Figure S6). We, therefore, conclude that ME boundary function is not affected by Dref and that the BEAF recognition motif present in ME boundary responds only to BEAF.…”
Section: Resultsmentioning
confidence: 82%
“…Why are there two such similar genes? Previously ANT-lacZ transgenic flies were shown to express lacZ widely throughout the developmental stages (23); however, recent postgenomic resources allow a more refined view. FlyAtlas, a comprehensive microarray-based atlas of gene expression in multiple Drosophila tissues (8), reports distinct expression patterns for sesB and ANT2 genes (Table 1).…”
Section: Resultsmentioning
confidence: 99%